(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
To improve levels of girls’ education, it is vital to widen the definition of child labour beyond wage employment. At present, there is little recognition of the economic contribution of girls to the economy and little effort has been made to get girls out of work and into school. There also remain long-standing stereotypes and norms that seek to discriminate against the girl child. However, the picture is not all bleak, for efforts at the grass roots level are afoot, wherein the NGOs have worked hand-in-hand with villagers to send their girls to school with very dramatic results.